Testicular Gangrene without Bowel Ischemia: A Rare Presentation of Neonatal Strangulated Inguinal Hernia - Mariya Jacob; Viju John (Journal of Indian Association of Pediatric Surgeons)
Inguinal neonatal hernias are common, but testicular gangrene without bowel involvement is rare. We report such a case of strangulated hernia where the bowel loop was healthy and viable but the testes was gangrenous. This case highlights testicular vascular compromise in neonatal strangulated inguinal hernias, even without bowel involvement.